Fostering Environmental Citizenship Through Faith : Exploring the practices of stewardship within the Green Anglicans Movement of Kenya - Flam, Rebekka (2022)
This research explores the nexus of environmental citizenship and faith-based ecological stewardship through a case study on the Green Anglicans Movement (GAM) of Kenya. Inspired by African relational concepts, such as Ubuntu and Ukama, and environmental citizenship theory, the practices and beliefs of GAM stewards are analyzed. 14 collaborative interviews with various stakeholders, including volunteers and religious leaders, as well as witnessing and experiencing among participants in Kenya, provide the data for this analysis. Data collection took place in Nairobi and the North Rift Valley of Kenya between September 2021 to May 2022. The study was conducted in collaboration with participants of GAM and Mwangaza Light, a social enterprise concerned with energy poverty alleviation and climate change mitigation in Kenya. Thematic analysis was used to explore the data. Three research questions are addressed in this thesis, with the overall objective to better understand stewardship from the perspective of participants and explore how environmental citizenship may or may not be cultivated through stewardship. The first research question centers the participants’ perspectives by asking: how do participants perceive the Green Anglicans Movement of Kenya? By illustrating the movement’s identity, successes, challenges, and vision for the future from the perspective of members, a greater understanding and context is established. Moreover, notions of stewardship and environmental citizenship begin to emerge through these narratives. The second research question asks: how is environmental stewardship understood by members of the Green Anglicans Movement of Kenya? Inspired by African ethics and environmental citizenship theory, two key themes emerge: relationality and care. These themes are explored through the participants’ descriptions of stewardship. Finally, the third research question asks: in what ways does environmental citizenship show through the participants’ stewardship in the Green Anglicans Movement of Kenya? During the analysis, elements from environmental citizenship theory are presented, leading to the suggestion that GAM, through notions of faith, responsibility, cooperation, participation, caretaking, and benefitting, may be fostering a form of environmental citizenship inspired by stewardship. This study illustrates that environmental citizenship for members of GAM is a relational practice that participants do, often in community, through efforts of care. By viewing both people and the natural world as part of creation, a more holistic approach of ecological management can be considered. Ultimately, this research can support the global initiative to mitigate climate change by better understanding the practices and aims of environmental stewards and how environmental citizenship may be encouraged through a faith-based movement. Though religion and specifically Judeo-Christian beliefs have been criticized as being partly the cause of our current ecological crisis, religious institutions, making use of their agency, can offer guidance and leadership in their communities and may have the power to influence attitudes towards the environment and climate change.